Measurement and Decomposition of Consumption Inequality in Nepal - Uprety, Pravat (Journal of Business and Social Sciences Research, 2019)
This study aims at computing, comparing and decomposing the different inequality indices by rural and urban areas, sex of household head and ecological belt, so that policy maker can make the policy to reduce the inequality in Nepal. This study is based on the raw data taken from the 3rd Nepal Living Standard Survey-2011 conducted by the Central Bureau of Statistics (CBS). The study has used real consumption as the main variable to measure the inequality. In most of the cases five measures of inequality; Coefficient of variation (CV), Quantile Ratio Index, Gini Index, Generalised Entropy Index with parameter 0 and 1 were computed. The Gini index, Theil’s L and Theil’s T indices are 0.328, 0.175 and 0.194, respectively. The study has found no significant difference in inequality between male- and female-headed households; and the inequality in urban areas is higher than that in the rural areas. By ecological belts, the inequality is highest in hills and lowest in mountains. The country should place focus on urban areas and hilly belt to reduce inequality.